Accessibility Measures to Opportunities in Urban Studies - Hishiyama, Jefferson (Corporación Universitaria del Caribe, CECAR., 2021)
This study aims to identify the approaches to measure accessibility, their indicators and main application themes in land use and transport systems. Through a hybrid method of systematic literature review and bibliometric analysis of bibliographic coupling networks, 54 publications were selected and 7 application themes were identified (public transport, transport systems, urban planning, land use, built environment, economic analysis and new technologies). The versatility of accessibility measures in urban studies was verified and there was a greater opportunity for scientific contribution in emerging themes related to new technologies and their implications for urban and transport planning.